Assembly patterns of soil‐dwelling lichens after glacier retreat in the European Alps. (23rd February 2017) - Nascimbene, Juri; Mayrhofer, Helmut; Dainese, Matteo; Bilovitz, Peter Othmar
Abstract: Aim: To assess the spatial‐temporal dynamics of primary succession following deglaciation in soil‐dwelling lichen communities. Location: European Alps (Austria, Switzerland and Italy). Methods: Five glacier forelands subjected to relevant glacier retreat during the last century were investigated. In each glacier foreland, three successional stages were selected at increasing distance from the glacier, corresponding to a gradient of time since deglaciation between 25 and 160 years. In each successional stage, soil‐dwelling lichens were surveyed within five 1 × 1 m plots. In addition to a classical ecological framework, based on species richness and composition, we applied a functional approach to better elucidate community assembly mechanisms. Results: A positive relationship was found between species richness and time since deglaciation indicating that richer lichen communities can be found at increasing terrain ageing. This pattern was associated with compositional shifts, suggesting that different community assemblages can be found along the successional stages. The analysis of β‐diversity revealed a significant nested pattern of species assemblages along the gradient (i.e. earlier successional stages hosted a subset of the species already established in older successional stages), while the turnover component was less relevant. Considering functional groups, we found contrasting patterns in relation to time since deglaciation: the incidence of species with a cyanobacterial photobiont and those reproducing by spores decreased, while that of species reproducing by vegetative propagules increased. Main conclusions: This study reveals that community assembly patterns of soil‐dwelling lichens in alpine glacier forelands are ruled by mechanisms of directional species accumulation and trait selection that involve a trade‐off between different functional strategies. Functional traits that reflect the dispersal and adaptation capability of the species underpin the colonization success of soil‐dwelling lichens in glacier forelands.